O dividual feminino a partir do filme-ensaio Elena (2012): uma noção traçada de forma ensaística em diálogo com diversas mulheres - Almeida, Letícia Benevides Araújo (2023)
This is my first essay. An attempt to find myself from a thinking-essayistic-affective writing. Coming into contact with the essay through the cinema has revived in me the desire to question myself and the world around me. In this writing, I joined eight women, Ana, Cecília, Dandara, Diana, Ket, Laura, Letícia (me), Pollyana and Virna, my affective subjects. Collectively, we thought about feminine issues based on the visualization of the essay-film Elena, directed by Brazilian filmmaker Petra Costa. We held two online meetings in which we presented images (photographs, cinematographic scenes, poetry, lesbopoesies, short stories, illustrations, paintings) that appeared as we watched Elena. With these images in hand, I began to walk the path in order to think about my problem-issue: the possibility of extending Deleuze's concept of the dividual by taking the feminine as a perspective. To this end, I brought the images of my affective subjects closer to blackboards and made visual montages inspired by Abby Warburg's Atlas Mnemosyne. In the gaps, traces, ashes that these approximations left, we perceive a plural, fluid, collective feminine, which is built from our occupations with the world. We realized that the affective essay methodology created here allowed our experiences to be exposed and seen as important, as dividual. We have seen that it is possible to think of the feminine dividual, which contemplates all the particularity of becoming a woman. My intention is not to exhaust this study, but to create others from this reflection. The feminine dividual is an open concept and can be judged, refuted, considered or be wrong.